2020
DOI: 10.1002/rem.21658
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting polycyclic aromatic hydrocarbon biodegradation by Aspergillus flavus

Abstract: This study investigated the ability of fungi isolated from highly contaminated soil to biodegrade polycyclic aromatic hydrocarbon (PAH) compounds, as well as the effect of several parameters on the biodegradation ability of these fungi. The isolated fungi were identified using ITS rDNA sequencing and tested using 2,6‐dichlorophinolendophenol to determine their preliminary ability to degrade crude oil. The top‐performing fungi, Aspergillus flavus and Aspergillus fumigatus, were selected to test their ability to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 38 publications
(53 reference statements)
1
2
0
2
Order By: Relevance
“…Comparing our findings with more recent studies and additional ecological data provided evidence for the ubiquitous dominance of Ascomycota and Basidiomycota in coastal habitats (Wang et al 2014), suggesting that members of these two phyla may play a major role in organic matter cycling (Wang et al 2019). Some fungal genera reported in the present study, such as Aspergillus (Gofar 2013;Al-Dossary et al 2020;Obi et al 2020), Candida (Chrzanowski et al 2005;Kaczorek et al 2008), Penicillium (Al-Dossary et al 2020Obi et al 2020), Pichia, and Yarrowia (Kutty and Philip 2008;Hassanshahian et al 2012;Kaczorek et al 2008) are capable of assimilating hydrocarbons while Malassezia was found to be active in carbon cycling of phytoplankton in coastal waters (Orsi et al 2022). On the other hand, several previous studies have shown the direct involvement of fungi in nitrogen metabolism, including ammonia assimilation and nitrate or nitrite denitrification (Wegley et al 2007;Maeda et al 2015;Civiero et al 2018).…”
Section: Correlation Between Fungal Communities and Environmental Fac...supporting
confidence: 87%
“…Comparing our findings with more recent studies and additional ecological data provided evidence for the ubiquitous dominance of Ascomycota and Basidiomycota in coastal habitats (Wang et al 2014), suggesting that members of these two phyla may play a major role in organic matter cycling (Wang et al 2019). Some fungal genera reported in the present study, such as Aspergillus (Gofar 2013;Al-Dossary et al 2020;Obi et al 2020), Candida (Chrzanowski et al 2005;Kaczorek et al 2008), Penicillium (Al-Dossary et al 2020Obi et al 2020), Pichia, and Yarrowia (Kutty and Philip 2008;Hassanshahian et al 2012;Kaczorek et al 2008) are capable of assimilating hydrocarbons while Malassezia was found to be active in carbon cycling of phytoplankton in coastal waters (Orsi et al 2022). On the other hand, several previous studies have shown the direct involvement of fungi in nitrogen metabolism, including ammonia assimilation and nitrate or nitrite denitrification (Wegley et al 2007;Maeda et al 2015;Civiero et al 2018).…”
Section: Correlation Between Fungal Communities and Environmental Fac...supporting
confidence: 87%
“…Hydrocarbonoclastic fungi isolated in this study, were linked to known PAH and/or hydrocarbon degraders. Aspergillus flavus can degrade kerosene 56 , aviation fuel 57 , benzo[a]pyrene, a 5-ring priority PAH and one of the most important industrial pollutants 58 and six other PAHs among the 16 priority PAHs 59 . Phoma sp.…”
Section: Discussionmentioning
confidence: 99%
“…O mecanismo utilizado pelos fungos para biodegradar os petroderivados pode ser observado pela incorporação de um aceptor de elétrons, como o DCPIP, indicada pela mudança da cor do meio, de azul escuro a incolor (Peixoto, et al, 2018;Ribeiro, et al, 2020). Assim, esta metodologia é considerada eficaz e tem sido amplamente utilizada na seleção de micro-organismos com potencial de biodegradação (Al-Nasrawi, 2012;El Hanafy, et al, 2015;Al-Dossary, et al, 2020;Ozyurek, et al, 2021).…”
Section: Biodegradação De Diesel E Queroseneunclassified
“…Dentre deles, os gêneros Aspergillus e Penicillium são considerados os mais eficientes na degradação de hidrocarbonetos, sendo relatados em inúmeras pesquisas (Saratale, et al, 2007;Al-Nasrawi, 2012;El Hanafy, et al, 2015;Ozyurek, et al, 2021). Representantes desses gêneros estão amplamente difundidos no ambiente, pois produzem estruturas reprodutivas em grande número e muito resistentes, que lhes permitem resistir a condições ambientais desfavoráveis, como baixa umidade, altas temperaturas e elevadas concentrações de petróleo bruto no solo, proporcionando-lhes uma vantagem competitiva para a sobrevivência em tais ambientes (Schwarz, et al, 2019;Al-Dossary, et al, 2020)…”
Section: Biodegradação De Diesel E Queroseneunclassified